J12 The perspective program: evaluating the effect of SAGE-718 on cognitive function in patients with Huntington's disease. (12th September 2022) - Koenig, Aaron; Stout, Julie; Johannesen, Jason; Petrillo, Jennifer; Li, Sigui; Pradhan, Pranoti; Lefler, Emily; Paumier, Katrina; Wald, Jeffrey; Quirk, Mike; Doherty, James
Abstract : Background: Cognitive impairment is a key driver of disability in patients with early-stage Huntington's disease (HD). SAGE-718 is an investigational NMDA receptor positive allosteric modulator that has been generally well tolerated and associated with improved cognitive performance in patients with HD and other neurodegenerative diseases in clinical studies conducted to date. Aims: The PERSPECTIVE Program comprises three complementary trials: two double-blind, placebo-controlled, Phase 2 studies (DIMENSION [NCT05107128 ; enrolling] and SURVEYOR [NCT05358821 ; enrolling]) and one Phase 3 open-label safety study (planned). DIMENSION and SURVEYOR are designed to evaluate the effect of SAGE-718 on cognitive performance and functioning in patients with HD and cognitive impairment. SURVEYOR will also evaluate the magnitude of baseline differences in cognitive performance between patients with HD and healthy participants (HPs) to inform the clinical meaningfulness of cognitive endpoints. Methods: The PERSPECTIVE Program design and key endpoints are summarized ( Figure 1 ). In DIMENSION and SURVEYOR, patients with HD will be randomized 1:1 to daily, oral SAGE-718 or placebo. In SURVEYOR, an additional non-interventional cohort of matched HPs will undergo assessment as a reference group on the performance scales. Patients with HD who complete either DIMENSION or SURVEYOR, together with a de novo cohort of patients with HD and normal Total Functioning Capacity (TFC = 13) and/or Montreal Cognitive Assessment (MoCA ≥26) scores, may enroll into an open-label, Phase 3 study evaluating the long-term safety and tolerability of SAGE-718. Conclusions: The PERSPECTIVE clinical development program will inform on the effectiveness of SAGE-718 in treating cognitive impairment associated with HD.